التغيرات الكونية في السنة النبوية: الآيات والمعجزات - الهذلي، معيضة بنت عابد بن مفلح (جامعة تكريت - كلية الآداب, 2022)
عنوان البحث: "التغيرات الكونية في السنة النبوية الآيات والمعجزات"، هذا البحث مقصور على الظواهر الكونية التي كان وقوعها من باب الإعجاز والتأييد للنبي (صلى الله عليه وسلم)، وإثبات نبوته، فالمقصود من البحث: هو كشف وجه الإعجاز في هذه الظواهر الكونية، وبيان نوعه في كل حديث تناوله البحث بالدراسة. يتكون البحث من مقدمة، وفصل، يضم أربعة مباحث، وخاتمة، وفهارس. الفصل الأول: التغيرات الكونية في معجزات النبي (صلى الله عليه وسلم)، وفيه ثلاثة مباحث: المبحث الأول: المعجزة، والفرق بينها وبين الخوارق الأخرى، وفيه ثلاثة مطالب، المبحث الثاني: تعريف التغير الكوني، وفيه ثلاثة مطالب، المبحث الثالث: أقسام التغيرات الكونية في السنة، وهي قسمان: القسم الأول تغيرات تقع بانفكاك عقد النظام الكوني، القسم الثاني: تغيرات حدثت في النظام الكوني دون انفكاك عقده، وهي أيضا نوعان: إما تغيرات علوية، وإما تغيرات سفلية، فالنوع الأول: تغيرات علوية: تتعلق بالسماء، والشمس، والقمر، والسحاب، والغمام، والريح، وفي هذا النوع أربعة مطالب، النوع الثاني: تغيرات سفلية: تتعلق بالأرض، وما فيها من جبال، وأحجار، ومياه، ونبات، وفي هذا النوع ثلاثة مطالب، المبحث الرابع: ما وقع لبعض أتباعه من كرامات تتعلق بالتغير الكوني، وفيه أربعة مطالب. وقد تضمن البحث عدة نتائج أهمها: 1. أن المعجزة تشترك مع الخوارق الأخرى في خرق العادة، والخروج عن المألوف، وتختلف عنها في أمور أخرى كثيرة. 2. أنه ما من آية أعطاها الله لنبي من الأنبياء السابقين، إلا وقد أعطى لنبينا (صلى الله عليه وسلم) مثلها، بل ربما خصه بمعجزات لم يؤتها نبي قبله. 3. أن حادثة الإسراء والمعراج آية عظيمة من معجزات رسول الله (صلى الله عليه وسلم) المتعلقة بالكون، أخبر عنها القرآن، وجاء ذكرها في صحاح الأخبار، وقد كانت تسلية لرسول الله (صلى الله عليه وسلم)، من تكذيب قومه، ودليلا على صحة نبوته، وفتنة للكافرين. 4. أن انشقاق القمر آية عظيمة، لا يكاد يعدلها شيء من آيات الأنبياء، وذلك أنه ظهر في ملكوت السماء، خارجا عن جملة طباع ما في هذا العالم المركب من الطبائع، فليس مما يطمع في الوصول إليه بحيلة. والحمد لله رب العالمين.
The title of the research: “Cosmic Changes in the Prophetic Sunnah, Verses and Miracles.” This research is limited to cosmic phenomena whose occurrence was a matter of miraculousness and support for the Prophet صلى الله عليه وسلم)), and to prove his prophet hood. The study dealt with it. The research consists of an introduction, a chapter, comprising four sections, a conclusion, and indexes. The First Chapter: the cosmic changes in the miracles of the Prophet (صلى الله عليه وسلم) and in it there are three sections: The first topic: the miracle, and the difference between it and other miraculous things, and in it there are three demands. Two sections: The first section is changes that occur by the rupture of the knots of the cosmic system, the second section: Changes that occurred in the cosmic system without its knots being untied, and they are also of two types: either upper changes, or lower changes, the first type: upper changes: related to the sky, the sun, the moon, and the clouds, Clouds, and wind, and in this type there are four demands, the second type: lower changes: related to the earth, and what is in it of mountains, stones, water, and plants, and in this type there are three demands, the fourth topic: the dignity that happened to some of his followers related to cosmic change, and in it Four demands. The research included several results, the most important of which are: 1. The miracle is in common with other supernatural beings in breaking the habit and deviating from the norm, and differs from it in many other matters. 2. There is no verse that God gave to one of the previous prophets, except that He gave our Prophet ( (صلى الله عليه وسلمthe like of it, and perhaps he singled out miracles that were not given to a prophet before him. 3. The incident of Al-Isra and Al-Miraj is a great sign of the miracles of the Messenger of God, peace be upon him, related to the universe. The Qur’an talked about it, and it was mentioned in the Sahih of Al-Akhbar. It was a comfort for the Messenger of God, peace be upon him, from the denial of his people, evidence of the validity of his prophet hood, and a trial for the unbelievers. 4. The splitting of the moon is a great sign, hardly any of the signs of the prophets can equal it, and that is because it appeared in the kingdom of heaven, out of the general nature of what is in this complex world of natures, so there is nothing that he aspires to reach with a trick. Thank Allah the God of Everything.
Keywords: الشريعة الإسلامية -- السنة النبوية -- معجزات النبوة -- محمد، صلى الله عليه وسلم -- الآيات الكونية